Ayurvedic Approach in Thoracic Myelopathy - Febina NC; Sivakumar C.S; Aneesh S (International Journal of Ayurveda and Pharma Research, 2025)
Thoracic myelopathy is a disorder characterized by spinal cord compression occurring in the thoracic region of the spine. It is relatively rare due to the limited degenerative changes that occur at this level of the spine, largely because the rib cage restricts movement in that area. A 54-year female patient complaint of burning pain over bilateral foot since 1 year and aggravated since 3-4 months, weakness of bilateral lower limbs for 3 months, loss of sensation over lower back, lower abdomen, bilateral lower limbs for 2weeks, urinary retention and feacal incontinence for 2 weeks came to the OPD of our hospital. The condition was diagnosed as thoracic compressive myelopathy through clinical examination and MRI spine. On the basis of clinical feature condition is similar to Kaphavrutha vata in Ayurveda. Patient underwent Ayurvedic treatment modalities Rooksha swedam (dry sudation using medicinal powder), Sankara sweda, Dasamoola kashaya dhara, Abhyangam (oil massage), Matravasthi (oil enema) and Kayasekam. After treatment symptoms reduced and Sensory, motor and autonomic functions improved. The treatment outcome suggests that ayurvedic treatment modalities can be a valuable alternative management for spinal cord disorder.